Acute effects of soccer training on white blood cell count in elite female players - Avloniti, A. A.; Douda, H. T.; Tokmakidis, S. P.; Kortsaris, A. H.; Papadopoulou, E. G.; Spanoudakis, E. G. (International Journal of Sports Physiology and Performance, 2007)
To investigate the acute changes in leukocyte number and cortisol after a single bout of soccer training. Methods: Ten elite female national-team soccer players and 8 nonathletes participated in the study. The duration of the exercise was 2 h, and it was performed at an intensity of 75% of maximal heart rate (HRmax). Blood samples were taken before, immediately after, and 4 h after a soccer training session to determine total white blood cells; the subsets of neutrophils, lymphocytes, monocytes, eosinophils, and basophils; and cortisol.At the same time, blood samples were obtained from nonathletes who refrained from exercise. Results: Data analysis indicated a significant increase in total white blood cells in the athletes postexercise (P < .001). The leukocytosis was still evident after 4 h of recovery (78% higher than the preexercise values), and there was a significant difference between athletes and nonathletes (P < .001). This leukocytosis was primarily caused by neutrophilia—there were no significant differences in lymphocytes after the end of exercise or between the 2 groups (P > 0.05). In addition, there was a statistically significant difference in cortisol concentration between athletes and nonathletes after the exercise (P < .001). Conclusion: These findings revealed that the single bout of soccer training at an intensity of 75% of HRmax induced leukocytosis without affecting the lymphocyte count in elite female athletes and probably the effectiveness of cellular components of adaptive immunity. Coaches should provide adequate time (>4 h) until the next exercise session.